Error Analysis of Narrowband Power-Line Communication in the Off-Grid Electrical System - Blazek, Vojtech; Slanina, Zdenek; Petruzela, Michal; Hrbáč, Roman; Vysocký, Jan; Prokop, Lukas; Misak, Stanislav; Walendziuk, Wojciech (Sensors (Basel, Switzerland), 2022)
Narrowband power-line communication seems to be a suitable communication technology designed for off-grid renewable energy solutions. Existing electrical installations can be designed both for the transmission of electricity and for the communication of electrical equipment operating inside such an installation. This study presents an implementation of the above-mentioned off-grid communication system and examines the basic problems related to its exploitation. The authors of this article focused their attention primarily on examining the disturbance of the communication channel caused by the use of typical electrical devices, such as: a light bulb, a kettle, etc. used in a household. The aim of the research was also to find the impact of switching on individual devices and their combinations on the disturbances during data transmission. Measurements of incorrectly transmitted data packets were carried out and then the test results were referred to the error measures. Moreover, the influence of the carrier frequencies on the signal attenuation and the method of eliminating the existing interferences were also discussed.
Keywords: microgrid; počítačové systémy; Computer Systems; power line communication; komunikace; Electricity; Communication; elektřina; off-grid; obnovitelná energie; Renewable Energy